Visual function status in myopic patients before and after pharmacological correction of antioxidant defense system failure (Ukrainian Journal of Ophthalmology, 2026)
Background: Recent studies of the clinical features and pathogenesis of the acquired, progressive and complicated myopia have evidenced that patients with this disease have reduced antioxidant defense. It is hypothesized that pharmacological correction of antioxidant defense system failure will improve visual functions in myopes.Purpose: To assess the status of visual functions (including distance visual acuity, absolute reserve of accommodation and photopic light sensitivity) in patients with myopia of different degrees before and following treatment with an antioxidant medication (Fakovit).Materials and Methods: The Fakovit treatment group included 70 myopes (140 eyes) (mild myopes, n = 28; medium myopes, n = 22; high myopes, n = 20), whereas the control group included 30 aged matched myopes who did not receive Fakovit treatment. All patients underwent ophthalmic examinations including refractometry, biomicroscopy, echobiometry, ophthalmoscopy, and absolute reserve of accommodation. The uncorrected and corrected distance visual acuities (VA) were assessed using the Shevalev’s Chart, and absolute reserve of accommodation (RA) was assessed using a conventional technique. Photopic light sensitivity was assessed with the use of semi-automatic registering adaptometer.Results: An improvement in VA was achieved in 86.1% of mild and medium myopes of the treatment group. An improvement in and stabilization of RA was found in 44.4% (mainly, in mild myopes) and 38.8%, respectively, of the patients of the treatment group, and a 1.43±1.29-D reduction in RA (p < 0.05) was observed in the control group. Photopic light sensitivity of the visual system had a tendency to increase in all myopes after treatment with Fakovit (in particular, it increased statistically significantly by 0.16±0.04 log units in mild myopes), and did not change in the controls.Conclusion: Correction of antioxidant defense system failure with Fakovit improved and stabilized visual functions (visual acuity, reserve of accommodation, and photopic light sensitivity) in myopic patients.
Keywords: pharmacological correction; antioxidant defense system; reduced antioxidant defense; myopia